Građanska kultura i aktivizam – Uloga NGO - Donev, Dejan (My University, 2010)
There is no doubt that culture is a significant determinant, both for us and the society that produces it. However, the present, determined by an information chaos, tends to indicate a growing need for the reconsidering of this determinant of human existence. Because of the new changes in a system of values, citizens are questioned less and less about the sort of culture necessary to justify its existence and being, and consequentially as the producer of culture. In a quest for answers to this basic questions, we become increasingly aware of the fact that the culture of the society we belong to, exactly due to the incapability of this society to restore or offer an order of values in a disturbed value system, in decreasingly capable of offering the right culture, and increasingly offers a culture, which is a goal in itself, in order to preserve the social system and its economy. For that reason we will consider how and why NGOs become a vehicle for the correction of such a culture, through theirs activities and the answers they offer to the need s of human beings.
Civil Culture and Activism - The Role of NGOs
Keywords: Producing of culture, ethics, corrective, society, NGOs